Decoding the role of toxic coctails of metals in endocrine health: the study in the general population of the Republic of Serbia - Buha Djordjević, Aleksandra (Archives of Pharmacy, 2022)
The human population is exposed to a vast number of chemicals that are known or suspected endocrine disruptors. Although thresholds are mainly determined concerning a single compound, in real life we are indeed exposed to multiple chemicals in mixtures, i.e. toxic cocktails. The focus of this research was to determine the effects that toxic cocktails of metal(oid)s have on human endocrine health The study involved 435 participants from the general population of Serbia (218 women and 217 men) from five different cohorts (prostate and testes cancer patients, breast cancer and benign breast dysplasia, pancreatic cancer, thyroid, and metabolic disorders patients, and healthy volunteers).  Blood cadmium (Cd), lead (Pb), arsenic (As), mercury (Hg), nickel (Ni), and chromium (Cr) levels and serum levels of various hormones were measured in all collected samples. The statistical analyses were performed using the R language while dose-response analysis was performed in PROAST software. Levels estimated to produce the 10% extra risk of testosterone serum levels disturbances were lower than median Hg levels measured in the general population. The obtained results also provided support for the positive association between Pb exposure and higher insulin levels. Similarly, the calculated levels that can produce 10% of extra risk for the disturbances in free thyroxine levels were lower than the medium determined As levels. These findings provide strong support for the endocrine-disrupting effects of the investigated toxic cocktail of metal(oid)s present in our environment and suggest that threshold values for such effects might be lower than those currently implemented.